Authoritarian origins of democratic party systems in Africa - Riedl, Rachel Beatty (Cambridge University Press, 2014)
"Faced with a transition to multiparty democracy, many assume that breaking the power of incumbents is necessary to develop a stable, highly institutionalized party system. But, in fact, across Sub-Saharan Africa, the incumbent's demise is sufficient to ensure a highly volatile, weakly institutionalized party system in the democratic era. A strong authoritarian incumbent produces a more coherent, stable party competition, with the unintended consequences of promoting national territorial coverage; stronger partisan identities; opposition cohesion; and, ultimately, democratic accountability. In Ghana, for example, the incumbent military leader and authoritarian revolutionary J.J. Rawlings and his National Democratic Congress (NDC) party swept the founding elections in 1992. Since that time, Ghana has developed a highly institutionalized party system with low levels of volatility and an alternating majority between stable parties. Ghana has experienced two democratic turnovers, and the two major parties, the NDC and the New Patriotic Party (NPP), are deeply connected to their constituencies, they organize across the national territory to compete in every constituency, they mobilize participation during and beyond elections, and they aggregate coalitions of diverse citizens and interests. The NDC and the NPP alike are enduring entities that help shape individual partisan identities and structure national, regional, and local competition"--